2017
DOI: 10.1016/j.pbb.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the subjective effects of oral Δ9-THC in cannabis users

Abstract: Previous studies suggest that there are sex differences in endocannabinoid function and the response to exogenous cannabinoids, though data from clinical studies comparing acute cannabinoid effects in men and women under controlled laboratory conditions are limited. To further explore these potential differences, data from 30 cannabis users (N=18 M, 12 F) who completed previous Δ9-tetrahydrocannabinol (Δ9-THC) discrimination studies were combined for this retrospective analysis. In each study, subjects learned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 55 publications
4
60
0
1
Order By: Relevance
“…THC also is more potent in inducing acute antinociception and reducing inflammatory pain in female than in male rats (Craft et al, 2013a; Tseng and Craft, 2001). Preclinical results are consistent with findings from the human laboratory showing that women report greater sensitivity to the subjective effects of smoked cannabis (Cooper and Haney, 2014) and to lower doses of orally administered THC (Fogel et al, 2016); however, they are less sensitive than men to the subjective effects of higher doses of THC, an effect that the authors suggest may be related to greater tolerance at these doses (Fogel et al, 2016). Hence, although fewer women than men use cannabis for recreational purposes (SAMHSA, 2014), women may be more susceptible to developing addiction once use is initiated, a phenomenon that has been referred to as “telescoping” (Becker and Hu, 2008).…”
Section: 0 Introductionsupporting
confidence: 84%
“…THC also is more potent in inducing acute antinociception and reducing inflammatory pain in female than in male rats (Craft et al, 2013a; Tseng and Craft, 2001). Preclinical results are consistent with findings from the human laboratory showing that women report greater sensitivity to the subjective effects of smoked cannabis (Cooper and Haney, 2014) and to lower doses of orally administered THC (Fogel et al, 2016); however, they are less sensitive than men to the subjective effects of higher doses of THC, an effect that the authors suggest may be related to greater tolerance at these doses (Fogel et al, 2016). Hence, although fewer women than men use cannabis for recreational purposes (SAMHSA, 2014), women may be more susceptible to developing addiction once use is initiated, a phenomenon that has been referred to as “telescoping” (Becker and Hu, 2008).…”
Section: 0 Introductionsupporting
confidence: 84%
“…Similarly, a second study found that while prevalence of CUD was greater among males, females reported a shorter duration from onset of cannabis use to onset of CUD compared to men (mean of 5.8 vs. 4.7 years) [26]. Clinical research also indicates greater abuse liability among females, such that females reported greater subjective effects at lower doses of oral THC (5 mg), while males reported greater subjective effects at higher doses (15 mg) [27]. The authors suggest these sex differences in subjective effects may contribute to the more rapid progression to dependence (telescoping) observed in females [27].…”
Section: Cannabis Use Dependencementioning
confidence: 98%
“…Clinical research also indicates greater abuse liability among females, such that females reported greater subjective effects at lower doses of oral THC (5 mg), while males reported greater subjective effects at higher doses (15 mg) [27]. The authors suggest these sex differences in subjective effects may contribute to the more rapid progression to dependence (telescoping) observed in females [27]. Clearly, more robust research on cannabis telescoping is needed to inform tailored prevention and harm reduction approaches for women and girls, in particular.…”
Section: Cannabis Use Dependencementioning
confidence: 99%
“…Akin to other drugs of abuse, findings from multiple studies demonstrate that the reinforcing effects of cannabis and the subjective effects of THC may differ between males and females [14, 62, 63] and considerable pre-clinical data seemingly indicate that the ECS is sexually dimorphic [6467]. In the U.S., past-year prevalence of cannabis use and cannabis use disorder has increased in both males and females [1, 2].…”
Section: The Status Of Findings For Sex Differences In Cannabis Withdmentioning
confidence: 99%